2009
DOI: 10.1093/hmg/ddp121
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated muscle regeneration is a key factor in dysferlin-deficient muscular dystrophy

Abstract: Skeletal muscle requires an efficient and active membrane repair system to overcome the rigours of frequent contraction. Dysferlin is a component of that system and absence of dysferlin causes muscular dystrophy (dysferlinopathy) characterized by adult onset muscle weakness, high serum creatine kinase levels and a prominent inflammatory infiltrate. We have observed that dysferlinopathy patient biopsies show an excess of immature fibres and therefore investigated the role of dysferlin in muscle regeneration. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 47 publications
(60 reference statements)
3
75
0
2
Order By: Relevance
“…Second, increased susceptibility to contraction-induced injury of the muscle membrane is usually caused by the loss of the dystrophin-glycoprotein complex (DGC); however, dysferlin-deficient skeletal muscle possesses a structurally intact and stable DGC (11). Indeed, recent data showed that dysferlin-deficient skeletal muscles are equal to normal skeletal muscles in resistance to contraction-induced injury (18). However, following either 15 repetitive large-strain LCs or 150 small-strain LCs, dysferlin-null muscles were observed to experience a strong inflammatory response that delayed their recovery from injury caused by LCs (19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, increased susceptibility to contraction-induced injury of the muscle membrane is usually caused by the loss of the dystrophin-glycoprotein complex (DGC); however, dysferlin-deficient skeletal muscle possesses a structurally intact and stable DGC (11). Indeed, recent data showed that dysferlin-deficient skeletal muscles are equal to normal skeletal muscles in resistance to contraction-induced injury (18). However, following either 15 repetitive large-strain LCs or 150 small-strain LCs, dysferlin-null muscles were observed to experience a strong inflammatory response that delayed their recovery from injury caused by LCs (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Dysferlindeficient monocytes from SJL/J mice were reported to have increased phagocytic activity (26), and dysferlin deficiency induces an upregulation of inflammasome (27). However, a more recent study (18) did not find a difference in phagocytic activity of dysferlindeficient monocytes using C57BL/10-SJL.Dysf mice, which have a more controlled genetic background. Instead, the authors reported an impaired secretion of chemotactic molecules in dysferlindeficient myocytes, thus reducing neutrophil recruitment at an early stage of regeneration with subsequent incomplete muscle remodeling and ultimate inflammatory responses and develop-ment of muscular dystrophy (18).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that Ca 2+ influx through a plasma membrane breach triggers dysferlin-mediated membrane fusion to seal the lesion (Bansal et al, 2003;Glover and Brown, 2007;Lennon et al, 2003;McNeil and Kirchhausen, 2005). Alternatively, an indirect role for dysferlin in wound repair may involve intercellular signaling (Chiu et al, 2009). For example, upon plasma membrane wounding a cell might release factors that signal other cells to compensate for the impairment or loss of the wounded cell.…”
Section: Introductionmentioning
confidence: 99%
“…Dysferlin localizes to the plasma membrane and to the T-tubule membrane in striated muscle (Ampong et al, 2005;Anderson et al, 1999;Klinge et al, 2008), and transits to late endosomes, similar to myoferlin (Redpath et al, 2016). Dysferlin acts at intracellular membranes (Bansal et al, 2003;Marty et al, 2013), and the alteration of this process is held responsible for a defect in membrane repair (Bansal et al, 2003;Cooper and Head, 2014) during muscle regeneration (Chiu et al, 2009), and for changes in T-tubule morphology and the function of dysferlin-deficient muscle (Klinge et al, 2010b;Roostalu and Strähle, 2012). However, it is unknown how the dysferlin protein is mechanistically engaged in these functions (Al-Qusairi and Laporte, 2011; Kerr et al, 2014).…”
Section: Introductionmentioning
confidence: 99%